Prevalence of Gastrointestinal Parasites on Beef Cattle in Jombang District - Melda Mufidatul Ifqiyyah; Boedi Setiawan; Agus Wijaya (Universitas Airlangga, 2021)
The disease that is quite detrimental to cattle is gastrointestinal parasitic infection. Gastrointestinal parasites infect the cattle by taking host nutrients that would caused emaciation, lethargy, and decreased productivity. This study aims to determine the prevalence of gastrointestinal parasites in cattle in Jombang District. This research was conducted in July to August 2019 with 100 samples of cattle feces. Sample examinations were carried out in the laboratory of the Division of Veterinary Parasitology, Universitas Airlangga using the sedimentation and floating methods. Detection of parasites in all samples using microscope with magnification of 100x and 400x. On examination, several types of parasites were found included Strongyloides papillosus, Toxocara vitulorum, Oesophagostomum spp., Moniezia expansa, Blastocystis spp. and Eimeria spp. The results of this study were found the prevalence of gastrointestinal parasites on beef cattle in Jombang district was 35% with a worm infection prevalence of 15% and protozoan infections of 20%.